60%x+2/3x=1/3 . 6/1/3
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.


\(-5\left(x+\frac{1}{5}\right)-\frac{1}{2}\left(x-\frac{2}{3}\right)=\frac{3}{2}x-\frac{5}{6}\)
\(\Leftrightarrow-5x-\frac{1}{5}-\frac{1}{2}x+\frac{1}{3}=\frac{3}{2}x-\frac{5}{6}\)
\(\Leftrightarrow\left(-5x-\frac{1}{2}x\right)+\left(\frac{1}{3}-\frac{1}{5}\right)=\frac{3}{2}x-\frac{5}{6}\)
\(\Leftrightarrow\left(\frac{-10}{2}x-\frac{1}{2}x\right)+\left(\frac{5}{15}-\frac{3}{15}\right)=\frac{3}{2}x-\frac{5}{6}\)
\(\Leftrightarrow\frac{-11}{2}x+\frac{2}{15}=\frac{3}{2}x-\frac{5}{6}\)
\(\Leftrightarrow\frac{-11}{2}x-\frac{3}{2}x=-\frac{5}{6}-\frac{2}{15}\)
\(\Leftrightarrow\frac{-14}{2}x=-\frac{25}{30}-\frac{4}{30}\)
\(\Leftrightarrow-7x=-\frac{29}{30}\)
\(\Leftrightarrow x=-\frac{29}{30}\times\frac{-1}{7}\)
\(\Leftrightarrow x=\frac{29}{210}\)
\(3\left(x-\frac{1}{2}\right)-5\left(x+\frac{3}{5}\right)=-x+\frac{1}{5}\)
\(\Leftrightarrow3x-\frac{3}{2}-5x-3=\frac{1}{5}-x\)
\(\Leftrightarrow\left(3x-5x\right)-\left(\frac{3}{2}+3\right)=\frac{1}{5}-x\)
\(\Leftrightarrow-2x-\left(\frac{3}{2}+\frac{6}{2}\right)=\frac{1}{5}-x\)
\(\Leftrightarrow-2x-\frac{9}{2}=\frac{1}{5}-x\)
\(\Leftrightarrow-2x+x=\frac{1}{5}+\frac{9}{2}\)
\(\Leftrightarrow-x=\frac{2}{10}+\frac{45}{10}\)
\(\Leftrightarrow-x=\frac{47}{10}\)
\(\Leftrightarrow x=\frac{-47}{10}\)

1.
ĐKXĐ: \(x< 5\)
\(\Leftrightarrow\sqrt{\dfrac{42}{5-x}}-3+\sqrt{\dfrac{60}{7-x}}-3=0\)
\(\Leftrightarrow\dfrac{\dfrac{42}{5-x}-9}{\sqrt{\dfrac{42}{5-x}}+3}+\dfrac{\dfrac{60}{7-x}-9}{\sqrt{\dfrac{60}{7-x}}+3}=0\)
\(\Leftrightarrow\dfrac{9x-3}{\left(5-x\right)\left(\sqrt{\dfrac{42}{5-x}}+3\right)}+\dfrac{9x-3}{\left(7-x\right)\left(\sqrt{\dfrac{60}{7-x}}+3\right)}=0\)
\(\Leftrightarrow\left(9x-3\right)\left(\dfrac{1}{\left(5-x\right)\left(\sqrt{\dfrac{42}{5-x}}+3\right)}+\dfrac{1}{\left(7-x\right)\left(\sqrt{\dfrac{60}{7-x}}+3\right)}\right)=0\)
\(\Leftrightarrow x=\dfrac{1}{3}\)
b.
ĐKXĐ: \(x\ge2\)
\(\sqrt{\left(x-2\right)\left(x-1\right)}+\sqrt{x+3}=\sqrt{x-2}+\sqrt{\left(x-1\right)\left(x+3\right)}\)
\(\Leftrightarrow\sqrt{\left(x-2\right)\left(x-1\right)}-\sqrt{x-2}+\sqrt{x+3}-\sqrt{\left(x-1\right)\left(x+3\right)}=0\)
\(\Leftrightarrow\sqrt{x-2}\left(\sqrt{x-1}-1\right)-\sqrt{x+3}\left(\sqrt{x-1}-1\right)=0\)
\(\Leftrightarrow\left(\sqrt{x-1}-1\right)\left(\sqrt{x-2}-\sqrt{x+3}\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}\sqrt{x-1}-1=0\\\sqrt{x-2}-\sqrt{x+3}=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x-1=1\\x-2=x+3\left(vn\right)\end{matrix}\right.\)
\(\Rightarrow x=2\)

\(a.2|\frac{1}{2}x-\frac{1}{3}|-\frac{3}{2}=\frac{1}{4}\)
=> 2 / 1/2x - 1/3 / = 1/4 + 3/2 = 7/4
=> / 1/2x - 1/3 / = 7/4 : 2 = 7/8
=> \(\hept{\begin{cases}\frac{1}{2}x-\frac{1}{3}=\frac{7}{8}\\\frac{1}{2}x-\frac{1}{3}=-\frac{7}{8}\end{cases}}\)
=> \(\hept{\begin{cases}\frac{1}{2}x=\frac{7}{8}+\frac{1}{3}=\frac{29}{24}\\\frac{1}{2}x=-\frac{7}{8}+\frac{1}{3}=-\frac{13}{24}\end{cases}}\)
Đến đây ez rồi
So sánh x với 1/3 Vx đk : 60%x + 2/3x = 1/3.6
Ta có :
60%x + 2/3x = 1/3.6
=> 3/5x + 2/3x = 2
=> 19/15x = 2
=> x = 2 : 19/15
=> x = 30/19 = 1 + 11/19 > 1/3
<=> 60%x + 2/3x = 1/3 . 6 > 1/3

1,=\(x^2-3x-2x^2+6x=-x^2+3x\)
2,=\(3x^2-x-5+15x=3x^2+14x-5\)
3,=\(5x+15-6x^2-6x=-6x^2-x+15\)
4,=\(4x^2+12x-x-3=4x^2+11x-3\)
5: =>(x+5)^3=0
=>x+5=0
=>x=-5
6: =>(2x-3)^2=0
=>2x-3=0
=>x=3/2
7: =>(x-6)(x-10)=0
=>x=10 hoặc x=6
8: \(\Leftrightarrow x^3-12x^2+48x-64=0\)
=>(x-4)^3=0
=>x-4=0
=>x=4

a, 60%x + 2/3x =1/3.6 1/3
3/5x +2/3x =1/3.19/3
x.(3/5+2/3)=19/9
x.(9/15+10/15)=19/9
x.19/15=19/9
x=19/9:19/15
x=15/9
Vậy x=15/9
b,3.(3x-1/2)^3 +1/9=0
3.(3x-1/2)^3= -1/9
(3x-1/2)^3= -1/9:3
(3x-1/2)^3= -1/27
(3x-1/2)^3=(-1/3)^3
3x-1/2= -1/3
3x= -1/3-1/2
3x= -2/6+(-3/6)
3x= -5/6
x= -5/6 :3
x=-5/18
Vậy x=-5/18

a)(9x+2)x3=60
9x+2 =60:3
9x+2 =20
9x =20-2
9x=18
x=18:9
x=2

23.19 - 23.14 + 12020
= 23.(19 - 14) + 1
= 8.5 + 1
= 41
102 - [60: (56: 54 - 3.5)]
= 100 - [60: (52 - 15)]
= 100 - [60: (25 - 15)]
= 100 - [60 : 10]
= 100 - 6
= 94